2013
DOI: 10.1108/ijhcqa-04-2012-0035
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitude and practices among healthcare workers in a tertiary care hospital on needle stick injury

Abstract: This study analyses healthcare workers' NSI knowledge, attitude and practices, and also assesses their correlation with NSI incidence, which has not been done previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 24 publications
2
15
1
Order By: Relevance
“…In relation to chemical & biological hazards, this study clarified that, the most hazards facing nurses in their workplace were needle stick injury followed by MARS infection. This was in an agreement with Almurr, (2013); Bhargava et al (2013) and Eljedi (2015), who revealed in a similar study that, the prevalence of sharp injuries were high. Concerning to nurses' social & emotional hazards exposure, more than one third of nurses suffered from sadness & easy excitability as in (Figure 2).…”
Section: Discussionsupporting
confidence: 91%
“…In relation to chemical & biological hazards, this study clarified that, the most hazards facing nurses in their workplace were needle stick injury followed by MARS infection. This was in an agreement with Almurr, (2013); Bhargava et al (2013) and Eljedi (2015), who revealed in a similar study that, the prevalence of sharp injuries were high. Concerning to nurses' social & emotional hazards exposure, more than one third of nurses suffered from sadness & easy excitability as in (Figure 2).…”
Section: Discussionsupporting
confidence: 91%
“…In the event of a needle-stick injury, gloves act as a barrier or protection to minimize the amount of blood that might be transmitted during the needlestick injury [39,40]. Given the fact that a substantial proportion of healthcare staff directly involved with blood collection has at some time point been exposed to a needle-stick injury during their working time, wearing gloves sounds like a reasonable infection prevention measure [41,42]. The evidence also shows that the use of sterile gloves during blood collection for blood culture reduces the risk of contamination of the sample [43,44].…”
Section: Samplingmentioning
confidence: 99%
“…Several studies done to assess the knowledge, attitude and practice of doctors and other healthcare workers on specific occupational hazards like needle stick injuries and blood borne diseases have reported varying degrees of knowledge among different class of healthcare workers. 3,4,5 However, there is a paucity of literature on the effect of training on the knowledge and practices related to occupational health and safety. Our study showed that the workshop successfully increased the knowledge among the resident doctors regarding the importance of principles of ergonomics and measures to reduce and prevent occupational hazards.…”
Section: Discussionmentioning
confidence: 99%